ANALISIS EFISIENSI USAHATANI KARET (Hevea brasiliensis) DI DESA BIIH KECAMATAN KARANG INTAN PROVINSI KALIMANTAN SELATAN - Fenny Refiana (Fakultas Pertanian UVAYA Banjarmasin, 2020)
This research is about the analysis of rubber farming in Biih Village, Karang Intan, Kalimantan Selatan.The data taken is based on primary data and secondary data related to this research. Data analyzed were explicit costs, revenues, income and efficiency of this rubber farming using purposive sampling method with 29 respondents. The Total Exsplisit Cost is Rp.76,841,387.99 and Total Revenue is Rp.194,145,000,0 0 and the Total Income is Rp.117,3030,612 with an R / C ratio of 2.53 which means profitable rubber farming